PERAN PENDIDIKAN DAN PELATIHAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA KELURAHAN KELAYAN LUAR KECAMATAN BANJARMASIN TENGAH KOTA BANJARMASIN - Sri Mulyani; Rory Handriano; Sholihin Sholihin (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This study aims to determine and analyze the role of education and training in improving employee performance in Kelayan Luar Village, Central Banjarmasin District, Banjarmasin City. The problem faced is that in general employees in handling an activity have never done training in their field so that there is a lack of knowledge in that field. Personnel management training has never been carried out Administrative training has never been attended. The subjects in this study were employees of Kelayan Luar Village, Central Banjarmasin Subdistrict, Banjarmasin City as many as 20 employees of Kelayan Luar Village, Banjarmasin Tengah Subdistrict, Banjarmasin City. The method used in this study is a qualitative descriptive method. This method was chosen considering that this research is a descriptive study that aims to the role of education and training in improving employee performance in the Kelayan Luar Village, Banjarmasin Tengah District, Banjarmasin City. The results of the research are the On the job method by means of Coaching, Planned progression, Job Rotation, but for the Position Rotation of Civil Servants there has been a job rotation but only temporary if the civil servant concerned is on leave. Method Of the job so far, civil servants have never been instructed to learn by way of Executive Development Programs, Training, Organizational Development.